Crystal structure and defects visualization of Cu2ZnSnS4 nanoparticles employing transmission electron microscopy and electron diffraction. Issue 1 (November 2015) - Kattan, Nessrin; Hou, Bo; Fermín, David J.; Cherns, David
Abstract : Graphical abstract: Highlights: Fingerprint electron diffraction patterns for kesterite/stannite CZTS. Clear contrast with ZnS secondary phase. Visualization of defects in CZTS in the transition from nano to microcrystal. Observation of preferential crystal growth on {112} planes. Abstract: A detailed analysis of the structure of Cu2 ZnSnS4 (CZTS) nanocrystals synthesized by hot-injection in the presence of oleylamine is provided employing high resolution TEM, selected area electron diffraction (SAED) and convergent beam electron diffraction (CBED). The nanostructures were investigated as-grown and after vacuum thermal treatment at 550 °C. As-grown materials consisted of polycrystalline particles with an average size of 7 ± 3 nm, which grow an average size of 53 ± 13 nm after the vacuum annealing step. This thermal treatment allows investigating the initial stages of high quality film growth required in photovoltaic devices. Sets of SAED and CBED patterns, where individual crystals after annealing were viewed down different prominent zone axes, enabled us to reveal the presence of weak reflections due to cation ordering, and confirm a tetragonal unit cell consistent with either the kesterite or stannite structure. We demonstrate how these approaches enable to distinguish CZTS from secondary phases such as ZnS. Structure defects of partially annealed CZTS crystals were also investigated using bright and dark field images taken in 2-beam diffraction conditions as well as by high resolution lattice imaging. The material exhibited dislocations, along with lamellar twins and stacking faults characterized by local hexagonal structure on {112} planes. High resolution TEM images showed preferential growth on {112} planes during vacuum annealing, which is consistent with X-ray diffraction patterns. These studies provide key information on nanoscale crystal defects which may have important consequence on the performance of CZTS photovoltaic devices.